Physiological Workload Analysis of Mizusumashi Operators at PT. XYZ Using CVL and Work Energy Expenditure Methods - Maulana Ardi Hidayanto; Musfikotun Al Khikmah; Hanif Rizki Muhidin; Rafly Qusyiari; Yudi Prastyo (Jurnal Sains dan Teknologi (JSIT), 2026)
This research analyzes the physiological workload of the mizusumashi operator at PT. XYZ. An automotive manufacturing company. The work process of the mizusumashi operator requires the operator to work for 8 hours by lifting production materials and supplying production materials to the main line with a load of approximately 10-15 kg per box, which has the potential to cause physical fatigue and occupational diseases. The purpose of this research is to identify the level of physiological workload experienced by the mizusumashi operator using two research methods. The research methods used include the measurement of ten pulses, the calculation of the cardiovascular load percentage, and also the calculation of work energy expenditure using the pulse rate. The calculation results show that the CVL percentage is 34.5%, which means this indicates that the physiological workload is classified as a moderate workload with a fatigue level within safe limits. The results of the calculation using the work energy expenditure calculation show that the operator experiences a physiological workload in the very heavy workload category because the operator expends work energy of >500 kcal/hour, which means it causes high physical fatigue and the risk of physical injury. Based on these calculation results, changes to the mizusumashi operator's workstation are recommended so that the work is more ergonomic, comfortable, safe, and avoids workplace accidents and occupational diseases.